American society of clinical oncology update on the role of bisphosphonates and bone health issues in women with breast cancer Part II. Bisphosphonates in the adjuvant therapy of breast cancer - I. V. Vysotskaya (Опухоли женской репродуктивной системы)
American society of clinical oncology update on the roleof bisphosphonates and bone health issues in women with breast cancer Part II. Bisphosphonates in the adjuvant therapy of breast cancer